Book review: Where’s the ”math” in ”mathematics education”? Review of ”Mathematics and mathematics education: searching for common ground” - Aguilar, Mario Sánchez (NOMAD Nordic Studies in Mathematics Education, 2015)
Fried, M. N. & Dreyfus, T. (Eds.) (2014). Mathematics and mathematics education: searching for common ground. Dordrecht: Springer. https://doi.org/10.1007/978-94-007-7473-5